Flood Alert System Using IoT - Vandana, S; Deepak Raj, D; Rushika, B; Mano Venkatesh, V (International Journal of Computer Sciences and Engineering, 2025)
Majority of Dams are physically observed and are sending information with ordinary modes. Dam professionals need dam parameters information for their examination. In need, citizens are unconscious about dam parameters such as dam water level and entryway status. Due to the entangled and tedious process in a manual framework, a model for Remote Monitoring and Controlling of Dams is recommended that utilizations remote control innovation, connected to the web innovation, to accomplish extraordinary achievement in observing and controlling water levels in overseeing dams. To take care of these issues we are proposing framework which incorporates GUI programming at dam site. This innovation is utilized as a part of the water control and administration frameworks, where numerous specialists utilize manual frameworks for water control and administration. The purpose of our project is to monitor the level and flow of a dam using IoT in which the real time things are interconnected to the web employing Raspberry-pi.